Mineral assemblages as a record of the evolutionary history of the Pepper Mts. Shale Formation (the Holy Cross Mts.) - Naglik, Beata; Natkaniec-Nowak, Lucyna; Heflik, Wiesław (Geology, Geophysics and Environment, 2016)
The Pepper Mts. Shale Formation, consisting of: clayey shales, mudstones and sandstones, as one of the oldest unit of the Holy Cross Mts., was subjected to mineralogical and petrographical studies. In order to reconstruct the geological history of the succession, mineral assemblages were characterized from the genetic point of view. Pyrite and goethite taking a form of bacterial-cell pseudomorphoses, crystallized during sedimentation and/or diagenesis, while quartz, kaolinite, goethite and chlorite prove subsequent alteration due to the hydrothermal fluid circulation. Secondary sulphates occurring on the pyrite-bearing rock outcrops mark the way of weathering processes. According to the presented results, Cambrian sediments were affected by hot fluids, which caused mineral recomposition and maturing of organic matter. Under the hypergenic conditions sulphate crust precipitate with pickeringite [MgAl2(SO4)4 ∙ 22H2O], as a dominant phase accompanied by alunogen [Al2(SO4)3 ∙ 17H2O] and small amount of epsomite [MgSO4 ∙ 7H2O].